THE INSTITUTIONAL DIMENSIONS OF OPPRESSION: EXAMINING THE GENDER-RELATED IDEOLOGICAL FACTORS ASSOCIATED WITH VIOLENCE AGAINST GIRLS AT THE LEGAL AND POLITICAL LEVEL - Tchoukou, Julie Ada (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2022)
The problem of violence against girls in Nigeria has attracted scholarly attention from a number of empirical and theoretical vantage points. This scholarship is vitally important. It has helped thrust feminist and other anthropological discourse into an arena of anti-violence work with significant impacts on, and repercussions for, girls in Nigeria. However, despite systemic change over the past years, the problem of violence against girls in Nigeria — as in Africa generally — persists. A consensus has emerged in the literature that cultural and social norms are relevant to the persistence of violence against girls in Nigeria. Without understating that relevance, this article analyses the problem from a different perspective. Cultural, religious, ethnic, and social norms have figured increasingly in the conceptual frameworks of both international and national institutions, distracting attention from the ways in which ideologies confronting girls are actually embedded within organisational structures of control. Important as it may be to understand the ways that these norms have given rise to violence against girls, it is also vital to investigate the techniques through which violent practices are maintained despite the changing nature of Nigerian society. Using a critical legal studies approach, I argue that any solution to violence against girls must focus as much on institutional change as it does on social transformation. Exploring violence against girls from this perspective opens up an “institutional complex”, revealing a legal and political system that serves as a tool used by the government and the political elite for consolidating power and legitimising discriminatory principles as traditional values.